RASIO SUSU FULL CREAM DAN MINYAK SAWIT MERAH PADA PEMBUATAN ES KRIM UBI JALAR KUNING (Ipomea batatas L.) - Muhaiminati Adlina; Netti Herawati; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Ice cream is a semi-solid food made by freezing a mixture of milk, fats of animal and vegetable, sugar, and other foodstuffs. This study aims to get the best ratio between full cream milk and red palm oil. This research used a Complete Randomized Design (CRD) with four treatments and four replications. The treatment were ratio of full cream milk : red palm oil 100:0 (E0), 97:3 (E1), 94:6 (E2), 91:9 (E3). The data were statisticallyanalyzed using Analysis of Variance (ANOVA) and Duncan's New Multiple Range Test (DNMRT) at 5%. The research observed was overrun, melting rate, total solids, protein content, fat content, and sensory test. The best treatment of ice cream from this research was E2 which have overrun 23.45%, melting rate 12.47 minutes, total solids 33.01%, fat 5.17%, and protein 2.82%.The result of ice cream’s descriptive assesment testwere  yellow colour (2.83), taste sweet (2.50), slightly flavour red palm oil (3.33), and texture creamy (2.26). Overall assessment hedonic  test of ice cream was preferred by the panelists. Keywords : Ice cream, full cream milk, red palm oil